2006
DOI: 10.1176/ps.2006.57.10.1416
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Competitive Employment Outcomes for the Clubhouse and PACT Models

Abstract: Participants from both the PACT and clubhouse models achieved high employment levels, with no significant differences in weekly employment or 30-month job placement rates over the course of the study. During this time, clubhouse participants earned significantly higher wages and remained competitively employed for significantly more weeks per job than PACT participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 17 publications
2
20
1
1
Order By: Relevance
“…One randomised controlled trial compared a community treatment program (PACT) and a clubhouse as part of a study of supported employment (9). It was found that the PACT program retained more active participants.…”
Section: Employmentmentioning
confidence: 99%
“…One randomised controlled trial compared a community treatment program (PACT) and a clubhouse as part of a study of supported employment (9). It was found that the PACT program retained more active participants.…”
Section: Employmentmentioning
confidence: 99%
“…The model provides meaningful employment outcomes for its members, demonstrating higher wages and longer durations of employment when compared to similar programs like the Assertive Community Treatment (ACT) model (Schonebaum et al, 2006). Clubhouses operate at a fraction of the cost of ACT teams ($3,454 per member per year compared to $10,000-15,000 per member per year) highlighting the importance of preserving and protecting their services (National Alliance on Mental Illness [NAMI], 2007;Plotnick & Salzer, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…The Substance Abuse and Mental Health Services Administration (SAMHSA)-certified evidence-based model is a type of day treatment program for adults with mental illness that is characterized by a climate emphasizing personal strengths instead of deficits, the importance of interpersonal relationships, and the input and decision making of clubhouse members by engaging them in clubhouse clerical duties, reception, food service, transportation, and financial services (Jackson, 2001;SAMHSA, 2010). The intervention has proven effective for members in increasing employment, quality of life, and perceived recovery from mental illness (Macias et al, 2006;Mowbray, Woodward, Holter, MacFarlane, & Bybee, 2009;Schonebaum, Boyd, & Dudek, 2006). Clubhouses in North Carolina are threatened by significant local and state funding changes.…”
Section: Introductionmentioning
confidence: 99%
“…Clubhouse models of community support, such as Fountain House, can facilitate competitive employment. 1,16,17…”
Section: Pragmatic Outcomes and Psychiatric Rehabilitationmentioning
confidence: 99%